Day 2 Tue, October 01, 2013 2013
DOI: 10.2118/166072-ms
|View full text |Cite
|
Sign up to set email alerts
|

Gelled Emulsions of CO2-Water-Nanoparticles

Abstract: Enhanced oil recovery by CO2 injection is an effective method for recovering additional oil beyond waterflooding. In recent years it has garnered a lot of attention for two primary reasons: (a) the stable high price of oil and (b) environmental aspects of CO2 sequestration. Its use has been increasing steadily over the past few years. In many respects it is a win-win situation with CO2 sequestration and additional, incremental oil produced. However, the CO2-EOR process is handicapped, especially in thick reser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The harsh conditions such as reservoir temperature, high salinity, and surfactant adsorption to the rock may result in weak foam generation and therefore poor sweep efficiency. The use of nanoparticles may offer an alternative to surfactant to stabilize foam at harsh reservoir conditions. The nanoparticles can strongly adsorb at the interface and stabilize foams at high temepature and salinity. Also, the synergistic effect of surfactant and nanoparticles or the modification of the surface of solid nanoparticles through physiochemical interactions with surfactants may enhance foam stability and generate stronger foams than surfactants. Several studies reported the ability of mixtures of surfactant and nanoparticles to enhance the foam stability. Zhang et al (2008) used a mixture of laponite particles and surfactant, tetraethylene glycol monododecyl ether, and found an enhancement in foam stability under certain conditions .…”
Section: Introductionmentioning
confidence: 99%
“…The harsh conditions such as reservoir temperature, high salinity, and surfactant adsorption to the rock may result in weak foam generation and therefore poor sweep efficiency. The use of nanoparticles may offer an alternative to surfactant to stabilize foam at harsh reservoir conditions. The nanoparticles can strongly adsorb at the interface and stabilize foams at high temepature and salinity. Also, the synergistic effect of surfactant and nanoparticles or the modification of the surface of solid nanoparticles through physiochemical interactions with surfactants may enhance foam stability and generate stronger foams than surfactants. Several studies reported the ability of mixtures of surfactant and nanoparticles to enhance the foam stability. Zhang et al (2008) used a mixture of laponite particles and surfactant, tetraethylene glycol monododecyl ether, and found an enhancement in foam stability under certain conditions .…”
Section: Introductionmentioning
confidence: 99%
“…This defeats the sole reason of HCl usage since matrix acidizing cost increases as carbonic acid is much expensive compared to HCl for equivalent amount of rock dissolved (Chang et al 2008;Raj and Pal 2014). Modified acid is investigated on improving the efficiency of matrix acidizing (Zakaria and Nasr-El-Din 2016;Al Otaibi et al 2013;Carpenter 2014). The study does not comprehend the issue of CO 2 gas release from the reaction between HCl acid and carbonate rock.…”
Section: Carbonate Reservoirs and Matrix Acidizingmentioning
confidence: 99%
“…Al Otaibi et al used two kinds of Aerosil fumed and Ludox colloidal silica nanoparticles to screen the possibility of generating both water-in-CO 2 and CO 2 -in-water emulsions. 48 They used hydrophilic nanoparticles in the water/isooctane system to generate water-in-CO 2 emulsion. The other emulsion, CO 2 -in-water emulsion, was formed using hydrophilic nanoparticles in the same water/isooctane system.…”
Section: Introductionmentioning
confidence: 99%
“…So far, research on the conformance control by CO 2 emulsion is rare. Al Otaibi et al used two kinds of Aerosil fumed and Ludox colloidal silica nanoparticles to screen the possibility of generating both water-in-CO 2 and CO 2 -in-water emulsions . They used hydrophilic nanoparticles in the water/isooctane system to generate water-in-CO 2 emulsion.…”
Section: Introductionmentioning
confidence: 99%